Acute Pancreatitis Case Presented with Epileptic Seizure - Uygar Utku; Besime Utku (Türk Nöroloji Dergisi, 2013)
Acute pancreatitis, defined as the acute non-bacte¬rial inflammatory condition of the pancreas. A 53-year-old woman was admitted to our emergency service after a first episode of generalized tonic-clonic seizure. There was no past medical history. The initial laboratory findings showed a low serum calcium level (5.8 mg/dL normal value 8.8-10.2 mg/dL). High Amylase-802 U/L, Lipase-489 U/L levels. CT abdomen showed pancreatic edema and inflammation suggestive of acute pancreatitis. This case report demonstrates a rare but important differential diagnosis in generalised tonic-clonic seizures of adult onset